Who Governs Rural Russia? : Preliminary Outcomes of the 2006 Decentralization Reform - World Bank (World Bank, Moscow, 2017)
The objectives of the study are to: a) increase understanding of the effects and effectiveness of the implementation of the local government reform launched in 2006; and b) assess the impact of a World Bank-supported intervention that aimed to enhance effectiveness of the reforms by increasing local capacity and local participation. In line with these objectives, the study assessed the perceived effects and effectiveness of the implementation of the local government reform in selected provinces. The study also constitutes a baseline to allow for on-going assessment of progress and to inform corrective policy actions. The instruments and methods created during the study may be used in future assessments of the dynamics of local governance reform. These effects are reviewed in section two. The study also carried out a rigorous evaluation of the impact of an operational intervention carried out with World Bank support in the three regions of the study. This grant-funded project was aimed at increasing the effectiveness of participation of rural citizens in public life and increasing the capacity of local administrations to operate in the new legal and fiscal environment created by the decentralization reform. The summary of the impact evaluation can be found in section three.